Building bridges or digging the trench? International organizations, social media, and polarized fragmentation - Matthias Ecker-Ehrhardt (The Review of International Organizations, 2023)
Communication departments of international organizations (IOs) are important intermediaries of global governance who increasingly use social media to reach out to citizens directly. Social media pose new challenges for IO communication such as a highly competitive economy of attention and the fragmentation of the audiences driven by networked curation of content and selective exposure. In this context, communication departments have to make tough choices about what to communicate and how, aggravating inherent tensions between IO communication as comprehensive public information (aimed at institutional transparency)—and partisan political advocacy (aimed at normative change). If IO communication focuses on advocacy it might garner substantial resonance on social media. Such advocacy nevertheless fails to the extent that it fosters the polarized fragmentation of networked communication and undermines the credibility of IO communication as a source of trustworthy information across polarized "echo chambers." The paper illustrates this argument through a content and social network analysis of Twitter communication on the Global Compact for Safe, Orderly and Regular Migration (GCM). Remarkably, instead of facilitating cross-cluster communication ("building bridges") Twitter handles run by the United Nations Department of Global Communications (UNDGC) seem to have substantially fostered ideological fragmentation ("digging the trench") by their way of partisan retweeting, mentioning, and (hash)tagging.
Keywords: 320; International organizations; Social media; Public communication; Echo chambers; Advocacy; United Nations; Global Compact for Migration; Content analysis; Supervised machine learning; Social network analysis